The Development of Mathematical Literation Instruments Based on Class IV Geometry Material Conservation - Prasetyo, Kakung; Masrukan, Masrukan; Sunawan, Sunawan (Universitas Negeri Semarang, 2019)
Mathematical-based conservation literacy instruments in elementary school (SD) that are valid, reliable and practical are not yet available. This study aims to develop mathematical literacy instruments based on the conservation of grade IV elementary geometry material validity, reliability, and practicality. This research method uses the R & D Development model of Borg & Gall. Research procedures include (1) preliminary studies; (2) Planning; (3) the development of a hypothetical model; (4) Review of hypothetical models; (5) Revision I; (6) limited trials; (7) Revision II; (8) Extensive trials; (9) Revised final model. The sample used for the study was 30 students for a small scale test and 119 students for a large scale test. Data collection techniques using interviews, observation, and tests. The results of the instrument are declared to be valid in content of 0.60. The estimated reliability of Inter Class Correlation (ICC) between assessors is 0.809. Small-scale tests show the value of Kaiser Meyer Olkin (KMO) of 0.653 and Barteletts test sig. 0,000. However, there is 1 item that has a value of Measures of Sampling Adequacy (MSA) <0.5. Large-scale tests show the value of Results (KMO) of 0.685 and Bartlett's Test sig. 0,000. All items obtain an MSA value of> 0.5. The instrument forms 3 components. The value of Eigenvalues ​​component 1 is 3,273, component 2 is 2,585, and component 3 is 1,562. The conclusion of this study is that the instruments developed proved to be valid, reliable and practical. Valid content based on expert judgment. Valid constructively by forming 3 factors. Reliable based on empirical tests. The instrument proved to be very practical based on teacher ratings. The instrument used by the teacher is used as a tool to measure mathematical literacy and improve students' mathematical abilities.